2014
DOI: 10.4236/wjcd.2014.48049
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension, Hypertension and Associated Cardiovascular Risk Factors among Adult Congolese Urban Dwellers: Results of the Vitaraa Study

Abstract: Objective: To assess the prevalence of prehypertension and hypertension, their determinants and associated cardiovascular risk factors in Congolese urban dwellers. Methods: From July 2007 to March 2008, we collected information on lifestyle habits, medical history and anthropometric data in 1292 household members of Adoula Quarter, Kinshasa, aged 20 years or more, 731 women (56.6%). We obtained measurements of BP, blood glucose, serum lipids and qualitative proteinuria. We defined blood pressure categories acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…Second, this study shows a very low proportion of hypertensive patients treated but with no improvement between the two survey periods. Those findings remain in line with other authors who documented a low proportion of people aware of their hypertensive status, and a low proportion of those who are treated [9, 3033] similar to Xing et al in China [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Second, this study shows a very low proportion of hypertensive patients treated but with no improvement between the two survey periods. Those findings remain in line with other authors who documented a low proportion of people aware of their hypertensive status, and a low proportion of those who are treated [9, 3033] similar to Xing et al in China [20].…”
Section: Discussionsupporting
confidence: 92%
“…Studies in the Democratic Republic of the Congo (DRC) have shown an increased prevalence of hypertension ranging from 2% in the rural Pygmy population in 1960 [8] to 30.0–41.4% in the current population [9–11]. However, the approaches used in these studies—including the collection of medical data—is unreliable and does not clearly show the risks of hypertension in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) was defined by a GFR-MDRD < 90 ml / min / 1.73m 2 and classified according to KDIGO 2012 as follows: stage 1: a≥GFR 90 m1 / min / l, 73m; stage 2: DFG 60 -89 m1 / minll, 73m 2 stage 3 to: DFG 45 -59 ml / minll, 73m 2 stage 3 b: DFG 30 -44 ml / minll, 73m 2 stage 4: DFG 15 -29 ml / min / l, 73m 2 and stage 5: DFG < l5ml / min / l, 73 m 2 12 [12,21].…”
Section: Operational Definitionsmentioning
confidence: 99%
“…That's why, in the 2014 World Congress of Cardiology held in Melbourne, hypertension has been called the scourge of the African continent. In the Democratic Republic of Congo (DRC), the prevalence of HTN increased from 5% in 1986 to 30% in 2006 and 2007 in some population based studies [14]- [16]. Nowadays, seven years after these studies, a higher prevalence is more than plausible hypothesis because since then there has been no real riposte to counter this threatening scourge.…”
Section: Introductionmentioning
confidence: 99%